2022
DOI: 10.1016/j.aninu.2021.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Zn-deficiency abolishes metabolic effects in offspring induced by diet type

Abstract: Accumulating evidence implicates that offspring are susceptible to paternal alterations in numerous fetal disorders, such as growth and metabolic defects. However, less study has been conducted to define the relationship between paternal zinc deficiency (ZnD) and energy metabolism of offspring. In the present study, we used a paternal ZnD exposure (Zn at 0.3 μg/g) model to test energy metabolism of male and female offspring with the intervention of diet type (high-fat diet and low-fat diet). Our results demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, we found that paternal n-3 PUFAs reduced leptin levels in adult offspring in a sex-specific manner, with effects on F1 males and F2 females. In keeping with this, peri-conceptional exposure to other nutritional changes (e.g., obesity, fructose-rich diet, and Zn deficiency) is sufficient to shape offspring expression patterns of metabolism-associated genes, characterized by impacts on males instead of females in the F1 generation (82)(83)(84)(85)(86). However, inconsistent results have also been reported, with female (but not male) offspring from fathers fed a high-fat diet before mating displaying impaired pancreatic β-cell function with increased body weight (87).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, we found that paternal n-3 PUFAs reduced leptin levels in adult offspring in a sex-specific manner, with effects on F1 males and F2 females. In keeping with this, peri-conceptional exposure to other nutritional changes (e.g., obesity, fructose-rich diet, and Zn deficiency) is sufficient to shape offspring expression patterns of metabolism-associated genes, characterized by impacts on males instead of females in the F1 generation (82)(83)(84)(85)(86). However, inconsistent results have also been reported, with female (but not male) offspring from fathers fed a high-fat diet before mating displaying impaired pancreatic β-cell function with increased body weight (87).…”
Section: Discussionmentioning
confidence: 98%